Pendampingan Pembelajaran Berbasis Lesson Study dan Penelitian Tindakan Kelas dalam Rangka Optimalisasi Kinerja Guru Mapel Bahasa Inggris - Siti Tarwiyah (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2016)
English Language Learning in some schools had not been conducted maximally.  One of the influencing factors was the pedagogic and professional competence of the teachers which had not met the standard as mentioned in the Permendikbud No 16 Year 2007. Lesson Study and Classroom Action was expected to enhance pedagogic and professional competence to meet the process standard and the quality of English teaching learning process in general.  The achievement indicators of this program were: (1) arranging lesson plan based on the requirement of process standard, (2) understanding and implementing contextual learning, (3) creating varied learning activities based on text-based learning, (4) choosing and developing learning media appropriately, (5) developing and delivering learning materials, (6) Arranging instrument and conducting assessment and evaluation, (7) doing reflective teaching, (8) enhancing teaching preparedness, (9) planning a Classroom Action Research.